Pushbacks as technology of domination: considering the European deportation regime - Basilien-Gainche, Marie-Laure (Annual review of law and social science, 2025)
Nourished by the philosophy of Michel Foucault, this article considers pushbacks as a technology of domination that contributes to the European deportation regime. As endemic violations of migrants’ human rights are documented at EU borders, notably with summary returns of undesirable third-country nationals, the article interrogates the way the European Union and its member states order their migration management and border control policies, examining the dynamics and logic of this mechanism of power. The production of pushbacks at the EU borders is considered: Because they appear to be systemic, they can be understood as endorsing a structural dimension. Their implication is also explored: The infringements of migrants’ fundamental rights can be seized as a vector of desubjectivation of the individuals they subjugate.